Effects of osmotic and thermal shock on the invasive aquatic mudsnail Potamopyrgus antipodarum: Mortality and physiology under stressful conditions - Paolucci, Esteban Marcelo (2020)
Invasive freshwater species, such as the exotic mollusc Potamopyrgus antipodarum (New Zealand mudsnail), can frequently survive under harsh conditions, including brackish and hypoxic environments. We experimentally assessed the effects of osmotic (0, 10, 20, 25 and 30 psu) and thermal (20 °C) shock on mortality, activity and physiology of P. antipodarum collected at Capitol Lake, Olympia, Washington, USA, during winter and spring seasons when environmental temperature was 5 and 10 °C respectively. We measured standard metabolic rate and enzymatic activities (malate dehydrogenase, lactate dehydrogenase, alanopine dehydrogenase) in snails after a 10-day acclimation period at high salinity. Significantly higher mortalities were observed at higher salinities; the strongest effects occurred on snails collected at the end of winter, and exposed to 30 psu and 20 °C (100% mortality in 3 days). When snails were collected during the spring, 100% mortality was observed after 40 days at 30 psu and 20 °C. Standard metabolic rates were significantly lower when snails were exposed to salinities of 25 and 30 psu, even after 10 days of acclimation. Enzymatic activities showed small but significant declines after 10 days at 30 psu reflecting the declines observed in overall metabolism. The physiological tolerances to temperature and salinity displayed by this population of P. antipodarum make its eradication from Capital Lake difficult to achieve.